2018
DOI: 10.1080/09602011.2017.1422272
|View full text |Cite
|
Sign up to set email alerts
|

The neuropsychological rehabilitation of visual agnosia and Balint’s syndrome

Abstract: Visual agnosia and Balint's syndrome are complex neurological disorders of the higher visual system that can have a remarkable impact on individuals' lives. Rehabilitation of these individuals is important to enable participation in everyday activities despite the impairment. However, the literature about the rehabilitation of these disorders is virtually silent. Therefore, the aim of this systematic review is to give an overview of available literature describing treatment approaches and their effectiveness w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…However, individual case reports pointing out different rehabilitation protocols have come to show similarity among their treatment approaches. Among one of them applying visuo-perceptual retraining and a functional adaptation program to restore functionality (7) .…”
Section: Discussionmentioning
confidence: 99%
“…However, individual case reports pointing out different rehabilitation protocols have come to show similarity among their treatment approaches. Among one of them applying visuo-perceptual retraining and a functional adaptation program to restore functionality (7) .…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous recovery is rare in visual object agnosia, increasing the importance of special training sessions with patients [2,8]. Nevertheless, very little attention is paid to methods of restoration or compensation of visual gnosis, much less than to visual neglect correction issues, for example [7]. Indeed, in 2018, Heutink et al found only seven works on rehabilitation of patients with visual object agnosia in scientific publications [8].…”
Section: Rehabilitation Of Patients With Visual Object Agnosiamentioning
confidence: 99%
“…Since visual agnosia is a monomodal disorder, clinical cases of patients having signs of gnostic function disorder of other modalities along with visual gnostic disorders should not be regarded as cases of true visual agnosia, according to some experts [3]. Visual agnosias can be observed in the clinical picture of many brain diseases and lesions, nevertheless, they are still among the least studied disorders in neurology [7]. However, the relevance of timely diagnosing visual gnostic disorders is determined by their negative impact on the quality of life of patients and the need for early correction [8].…”
Section: Introductionmentioning
confidence: 99%
“…In these children, visual agnosia is considered a developmental disorder that becomes evident when the child becomes older and may appear as the difficulty to recognize quite specific objects, letters, or people [12] , [13] . Visual agnosia in children, acquired after a period of normal development, is not often reported [14] .…”
Section: Introductionmentioning
confidence: 99%